Depiction of ascetic figures on the recesses - Temples of India Project Team (Jio Institute, 2024)
View of the west-facing jangha (wall) of the Jain Temple where the bhadra (central projection) niche is empty but the intermediate and corner projections have sculptures on both its sides. The intermediate projections have depictions of dikpalas (deities of the cardinal directions). The recesses have depictions of ascetic figures.